Seismic and spectroscopic analysis of nine bright red giants observed by Kepler - Coelho, Hugo; Miglio, A; Morel, T; Lagarde, N; Bossini, D; Chaplin, W J; Degl’Innocenti, S; Dell’Omodarme, M; Garcia, R A; Handberg, R; Hekker, Saskia; Huber, D; et al. (Monthly notices of the Royal Astronomical Society, 2024)
ABSTRACT - Photometric time series gathered by space telescopes such as CoRoT and Kepler allow to detect solar-like oscillations in red giant stars and to measure their global seismic constraints, which can be used to infer global stellar properties (e.g. masses, radii, and evolutionary states). Combining such precise constraints with photospheric abundances provides a means of testing mixing processes that occur inside red-giant stars. In this work, we conduct a detailed spectroscopic and seismic analysis of nine nearby (d < 200 pc) red giant stars observed by Kepler. Both seismic constraints and grid-based modelling approaches are used to determine precise fundamental parameters for those evolved stars. We compare distances and radii derived from Gaia Data Release 3 parallaxes with those inferred by a combination of seismic, spectroscopic, and photometric constraints. We find no deviations within errors bars, however the small sample size and the associated uncertainties are a limiting factor for such comparison. We use the period spacing of mixed modes to distinguish between ascending red-giants and red clump stars. Based on the evolutionary status, we apply corrections to the values of Δν for some stars, resulting in a slight improvement to the agreement between seismic and photometric distances. Finally, we couple constraints on detailed chemical abundances with the inferred masses, radii, and evolutionary states. Our results corroborate previous studies that show that observed abundances of lithium and carbon isotopic ratio are in contrast with predictions from standard models, giving robust evidence for the occurrence of additional mixing during the red-giant phase.
Online veröffentlicht: 04 December 2023
Gesehen am 30.09.2024